2020
DOI: 10.1186/s12967-020-02515-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the two most frequent HLA haplotypes in the Italian population to the differential regional incidence of Covid-19

Abstract: Background Understanding how HLA polymorphisms may affect both susceptibility, course and severity of Covid-19 infection could help both at the clinical level to identify individuals at higher risk from the disease and at the epidemiological one to explain the differences in the epidemic trend among countries or even within a specific country. Covid-19 disease in Italy showed a peculiar geographical distribution from the northern most affected regions to the southern ones only slightly touched. Methods In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 46 publications
5
109
2
3
Order By: Relevance
“…Three HLA-A alleles were highly overrepresented in these groups: HLA-A * 02:01 and HLA-A * 03:01 were tightly associated with low risk while HLA-A * 01:01 contributed to the high risk group. Connection of HLA-A * 01:01 and HLA-A * 02:01 alleles with COVID-19 morbidity and mortality was already mentioned in the existing literature, namely, frequency of HLA-A * 01:01 in Italian regions positively correlated both with the number of COVID-19 cases and deaths, while significant negative correlation was observed for HLA-A * 02:01 ( 13 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Three HLA-A alleles were highly overrepresented in these groups: HLA-A * 02:01 and HLA-A * 03:01 were tightly associated with low risk while HLA-A * 01:01 contributed to the high risk group. Connection of HLA-A * 01:01 and HLA-A * 02:01 alleles with COVID-19 morbidity and mortality was already mentioned in the existing literature, namely, frequency of HLA-A * 01:01 in Italian regions positively correlated both with the number of COVID-19 cases and deaths, while significant negative correlation was observed for HLA-A * 02:01 ( 13 ).…”
Section: Discussionmentioning
confidence: 78%
“…It was demonstrated that the number of peptides with a high interaction constant are connected with individual HLA genotypes: the more viral peptides with high affinity bind to HLA class I, the easier the course of the disease. It was also shown that the frequency of the occurrence of HLA-A * 01:01 and HLA-A * 02:01 alleles is related to the number of infections and mortality rate in different regions of Italy ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy might be attributed to the varying strength of the immune response to SARS-Cov-2 on the basis of different genetic or epigenetic backgrounds 22 24 . HLA haplotypes have been reported to be associated with the disease susceptibility 25 . A recent meta-analysis revealed that 21 genes involved in toll like receptors and C-lectin pathways were associated with severe COVID-19 26 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth nothing that bivariate correlation analysis among the regional frequencies of HLA-A*01:01g-B*08:01g-C*07:01g-DRB1*03:01g haplotype and incidence and mortality showed a cluster distribution, with the northern regions having the highest haplotype frequencies and the highest incidence and mortality, the central regions recording intermediate and the southern regions exhibiting the lowest values. The opposite frame was reported for the haplotype HLA-A*02:01g-B*18:01g-C*07:01g-DRB1*11:04g [ 56 ]. However, the alleles analyzed in this study HLA-A*02:01, HLA-B*08:01, HLA-A*01:01, HLA-B*18:01, HLA-C*07:01 are predicted to exhibit a good viral antigen presenting capacity, with HLA-A*02:01 offering the highest numbers of both tightly (dissociation constant < 50 nM, peptide number 267) and loosely (dissociation constant < 500 nM, peptide number 795) SARS-CoV-2 peptides [ 51 , 56 ], thus making the relationship between COVID-19 death rates and in silico estimated HLA antigen presenting capacity less clear.…”
Section: Hlamentioning
confidence: 94%
“…In Mexico, a statistically significant correlation was documented between HLA-DRB1*01:01 allele and the predicted fatality rate in hospitalized patients (R = −0.44, p = 0.02) [ 55 ]. Similarly, analyzing the HLA haplotype distribution in three Italian zones (northern, central and southern regions), the haplotype HLA-A*01:01g-B*08:01g-C*07:01g-DRB1*03:01g showed a positive correlation and the haplotype HLA-A*02:01g-B*18:01g-C*07:01g-DRB1*11:04g and a negative correlation with both COVID-19 incidence (number of cases/100,000 inhabitants) and mortality (number of deaths/100,000 inhabitants) at three out of four the analyzed timepoints (the first time point was reported to have no significant results because it was too premature) [ 56 ]. HLA-A*01:01, -B*08:01, -C*07:01,-DRB1*03:01, -DQA1*05:01 and -DQB1*02:01 is a common Caucasoid haplotype called 8.1 ancestral haplotype (AH).…”
Section: Hlamentioning
confidence: 99%